GE_GERICHTE P/20158/2022 vom 7. August 2025 - GE Cour de justice (2025)
CONCOURS D'INFRACTIONS;MISE EN DANGER DE LA VIE D'AUTRUI(ART. 129 CP);VIOLENCE CONTRE LES AUTORITÉS | CP.49.al3; aCP.129.al1; aCP.285